(untitled) (Journal of the College of Basic Education, 2022)
To assess level of job satisfaction among nurses who are working in psychiatric hospitals and its relationship with some of sample characteristics which are age, gender, educational level, marital status, monthly income.Methodology: A descriptive analytical study was conducted in Ibn-Rushd psychiatric teaching hospital and AL-Rashad psychiatric teaching hospital. A non-probability (purposive) sample consist of of 90 nurses from the two hospitals.A Self Administerd Questionnaire was constructed to achieve the purposes of the study.